The application of mechanobiotechnology for immuno-engineering and cancer immunotherapy - Yoon, Chi Woo; Pan, Yijia; Wang, Yingxiao (Frontiers in Cell and Developmental Biology, 2022)
Immune-engineering is a rapidly emerging field in the past few years, as immunotherapy evolved from a paradigm-shifting therapeutic approach for cancer treatment to promising immuno-oncology models in clinical trials and commercial products. Linking the field of biomedical engineering with immunology, immuno-engineering applies engineering principles and utilizes synthetic biology tools to study and control the immune system for diseases treatments and interventions. Over the past decades, there has been a deeper understanding that mechanical forces play crucial roles in regulating immune cells at different stages from antigen recognition to actual killing, which suggests potential opportunities to design and tailor mechanobiology tools to novel immunotherapy. In this review, we first provide a brief introduction to recent technological and scientific advances in mechanobiology for immune cells. Different strategies for immuno-engineering are then discussed and evaluated. Furthermore, we describe the opportunities and challenges of applying mechanobiology and related technologies to study and engineer immune cells and ultimately modulate their function for immunotherapy. In summary, the synergetic integration of cutting-edge mechanical biology techniques into immune-engineering strategies can provide a powerful platform and allow new directions for the field of immunotherapy.